Valuation of flexible leases for corporate tenants facing uncertainty in their required work space - Ashuri, Baabak (International Journal of Strategic Property Management, 2010)
A valuation approach is presented to price flexible leases with expansion, contraction, and/or cancelation options from the corporate tenant perspective. This model uses the real option valuation approach and determines the flexibility value or the option premium of a lease. This premium is the maximum amount of money that the tenant is willing to invest in incorporating a specific flexible feature in the leasing arrangement. Our model considers uncertainty in the rental market, as well as uncertainty about the firm’s required workspace in an integrated valuation framework. First Published Online: 18 Oct 2010